Lightweight application program interface (API) for extensible markup language (XML) (2005)
An architecture that leverages support for markup language operations, e.g., extensible markup language (XML) queries, via a lightweight application program interface (API). The API defines an object model that can simplify construction of XML values in languages that do not natively support XML. The novel aspects of the described innovation can enable query languages to be factored into general operations (e.g., mapping, filtering, sorting, and/or projection of functions) on collections on one hand, and a set of domain specific operations (e.g., navigation, construction and modification) on the elements of these collections on another hand. The subject API can support creation of XML data that is node centric (e.g., context-free). Accordingly, nodes do not have to be constructed within the context of a document. Additionally, aspects can enable expression-oriented interface mechanisms as opposed to the imperative statement-oriented style interfaces used in connection with traditional interface mechanisms (e.g., DOM).